2014
DOI: 10.5664/jcsm.4202
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Architecture Following a Weight Loss Intervention in Overweight and Obese Patients with Obstructive Sleep Apnea and Type 2 Diabetes: Relationship to Apnea-Hypopnea Index

Abstract: Study Objectives: To determine if weight loss and/or changes in apnea-hypopnea index (AHI) improve sleep architecture in overweight/obese adults with type 2 diabetes (T2D) and obstructive sleep apnea (OSA). Methods: This was a randomized controlled trial including 264 overweight/obese adults with T2D and OSA. Participants were randomized to an intensive lifestyle intervention (ILI) or a diabetes and support education (DSE) control group. Measures included anthropometry, AHI, and sleep at baseline and year-1, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Young et al reported that men had a four times higher risk of sleep-disordered breathing (polysomnographically defined AHI of five or higher) for each SD increase in BMI 41. These and other studies support our hypothesis that weight loss surgery can improve weight loss outcomes, and may have a role in treating or curing OSA 19–22. However, currently, there is no meta-analysis to confirm this hypothesis, and this study will be the first systematic review and meta-analysis to assess the safety and efficacy of weight loss surgery for OSA with obesity in adults.…”
Section: Discussionsupporting
confidence: 84%
“…Young et al reported that men had a four times higher risk of sleep-disordered breathing (polysomnographically defined AHI of five or higher) for each SD increase in BMI 41. These and other studies support our hypothesis that weight loss surgery can improve weight loss outcomes, and may have a role in treating or curing OSA 19–22. However, currently, there is no meta-analysis to confirm this hypothesis, and this study will be the first systematic review and meta-analysis to assess the safety and efficacy of weight loss surgery for OSA with obesity in adults.…”
Section: Discussionsupporting
confidence: 84%
“…Baseline characteristics, including demographics, anthropometry, OSA severity, sleep duration and architecture (TST, stage 1, 2, SWS, REM sleep), and HbA1c have been previously reported (Kuna et al, 2013, Shechter et al, 2014). No baseline between-group differences were observed.…”
Section: Resultsmentioning
confidence: 93%
“…However, in a secondary analysis, a minimum REM sleep duration threshold of 30 minutes was used as a requirement to calculate REM-AHI (Mokhlesi and Punjabi, 2012). Intrascorer reliability across the 4-year follow-up was assessed and confirmed (Shechter et al, 2014). …”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…After bariatric surgery, it has been shown that the severity and symptoms of OSA decrease or sometimes even completely resolve with successful weight loss [ 6 ]. Overnight polysomnography (PSG) is the gold standard for the diagnosis of OSA [ 7 , 8 ]. However, not all patients who are morbidly obese are routinely tested and diagnosed for OSA by a PSG test.…”
Section: Introductionmentioning
confidence: 99%